Can additional experienced staff reduce emergency medical admissions?. Issue 1 (20th January 2004) - Goodacre, S; Mason, S; Kersh, R; Webster, A; Samaniego, N; Morris, F
Abstract : Background: Increases in emergency medical admissions are placing a strain upon hospitals throughout the world. The aim of the study was to evaluate the effect of a new post, the "A&E physician", upon emergency medical admissions to a hospital. Methods: For six months the A&E physician workload was audited and a randomised controlled comparison undertaken. Days were randomised to "A&E physician present" or "A&E physician absent". The A&E physician recorded details of all patients referred for medical admission, any intervention made, and their disposal from A&E. Routine hospital data compared the mean daily number of medical admissions, non-medical admissions, and referrals to other hospitals. Results: 124 days were randomised: 59 to A&E physician present, 65 to A&E physician absent. The A&E physician received 581 referrals and intervened in the management of 142 (24%). Of these, 80 were discharged home, apparently saving 1.4 admissions per day. However, randomised comparison showed that presence of the A&E physician was associated with a reduction of only 0.7 medical admissions per day (95% CI −1.7 to 3.2, p = 0.561), and an increase of 1.1 non-medical admissions (95% CI −0.2 to 2.3, p = 0.09) and 0.3 transfers to other hospitals per day (95% CI zero to 0.6, p = 0.09). Overall, hospital admissions were increased by 0.9 per day when the A&E physician was present (95% CI −1.8 to 3.6, p = 0.5). Conclusion: Despite receiving many referrals and discharging a substantial proportion of these patients home, the A&E physician did not significantly change emergency medical admissions and may have increased admissions to other specialties.